2022
DOI: 10.3390/antibiotics11030357
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibiotic Residues in Blossom Honeys from Different Regions in Turkey by LC-MS/MS Method

Abstract: In the present study, a total of 80 commercial blossom honey samples were obtained from local markets in Ankara, Turkey. These honeys were analyzed for 35 important and risky antibiotics (sulfonamide, tetracycline, macrolide, cephalosporin, aminoglycoside, quinolone, nitrofuran, chloramphenicol, and anthelmintic groups) by the LC-MS/MS multi-antibiotic method. In addition to these analyses, pH measure, moisture, and electrical conductivity were determined in these honey samples. Finally, seven out of 35 antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…In our study, among the 8 pine honey samples, sulfadimidine antibiotic was found in one sample (I‐pine) at the amount of 16.82 μg/kg. Er Demirhan & Demirhan [23] reported the determination of 35 antibiotic residues in 80 commercial blossom honey samples produced in Turkey using the LC‐MS/MS system. In this study, antibiotic residues were found in 35 samples within the detection limits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, among the 8 pine honey samples, sulfadimidine antibiotic was found in one sample (I‐pine) at the amount of 16.82 μg/kg. Er Demirhan & Demirhan [23] reported the determination of 35 antibiotic residues in 80 commercial blossom honey samples produced in Turkey using the LC‐MS/MS system. In this study, antibiotic residues were found in 35 samples within the detection limits.…”
Section: Resultsmentioning
confidence: 99%
“…The sample preparation protocol applied to honey samples for the determination of antibiotic residues was validated according to manufacturer guidelines Jasem [22] and Er Demirhan & Demirhan [23] . This protocol provided simple and quick sample preparation which does not require the use of solid phase extraction (SPE) and immunoaffinity columns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 In addition, the overuse of antibiotics leads to increased bacterial resistance, which in turn poses a threat to human health. Although there are many analytical methods for antibiotic detection, such as high-performance liquid chromatography (HPLC), 36,37 liquid chromatography-tandem mass spectrometry (LC-MS), 38,39 enzyme-linked immunoassay, 40,41 colorimetric analysis 42,43 and electrochemical detection, [44][45][46] these methods are costly and need complex procedures, time-consuming sample pretreatment, professional operation and high instrument maintenance costs. Therefore, the development and establishment of simple, economical, rapid, and sensitive TC essays are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The European Union, the United States, and China have established maximum residue limits of 100 μg/kg SMZ [ 4 , 5 ]. In previous studies, researchers have used numerous methods for the detection and quantification of SMZ, including liquid chromatography–mass spectrometry (LC–MS), high-performance liquid chromatography (HPLC), and the enzyme-linked immunosorbent assay (ELISA) [ 6 , 7 , 8 ]. Although LC–MS and HPLC are sensitive and highly specific for SMZ, they require complicated operations and are not suitable for detection in large numbers of samples [ 9 ].…”
Section: Introductionmentioning
confidence: 99%